Is there an obesity-metabolic syndrome related glomerulopathy? - Ritz, Eberhard; Koleganova, Nadezda; Piecha, Grzegorz (Current opinion in nephrology and hypertension, 2011)
Purpose of review - There is an increasing evidence for a specific form of focal segmental glomerulosclerosis (FSGS) related to obesity. Its prevalence has progressively increased in past decades. This form of FSGS represents the tip of an iceberg: a much broader spectrum of renal malfunction is linked to visceral obesity, which is closely connected to, but not completely identical with, the concept of ‘metabolic syndrome’. - Recent findings - The obesity-associated FSGS (obFSGS) is characterized by massive proteinuria and glomerular lesions which are similar to but less pronounced than in idiopathic FSGS, but the long-term prognosis is still dubious. - The patholophysiology underlying obesity-associated renal pathology includes insulin resistance and salt sensitivity of blood pressure (BP); more recently adiponectin deficiency, hyperaldosteronism and many other pathogenetic factors have been identified. The abnormalities of renal structure in obese and morbidly obese individuals include increased kidney weight, glomerulomegaly, disorder of podocytes, mesangial expansion and more recently also abnormalities of the renal interstitium. This is accompanied by functional abnormalities, that is renal hyperperfusion, increased filtration fraction and albuminuria. Both obesity and metabolic syndrome have been identified as powerful predictors of chronic kidney disease (CKD) and end-stage renal disease (ESRD). This correlation is not fully explained by associated hypertension and prediabetes/diabetes. - Summary - The link between progressive kidney disease and visceral obesity is of enormous public health importance. Apart from causing obFSGS, obesity aggravates most primary kidney diseases. Beyond standard therapy and weight loss, bariatric surgery has recently emerged as a successful intervention for obFSGS.
Gesehen am 16.09.2022